Systemic Barriers and Technological Opportunities in Transforming Urban Logistics - Rismanto, Hilman (Sinergi International Journal of Logistics, 2024)
Urban logistics systems, particularly in the area of last-mile delivery, are undergoing rapid transformation driven by technological advancements such as automation, artificial intelligence, and big data analytics. This study employs a narrative review methodology to examine the interplay between technological innovations and systemic factors influencing logistics performance across urban environments. Literature was systematically gathered from major academic databases using strategic keyword combinations, focusing on social, economic, technological, and institutional dimensions. The results indicate that while emerging technologies significantly enhance delivery efficiency and operational reliability, their impact is often constrained by structural barriers including outdated regulations, limited infrastructure, and socio-economic disparities. Social acceptance, economic readiness, and institutional support emerge as crucial enablers of successful technology adoption. The discussion highlights the necessity for integrated frameworks that address these systemic issues, proposing policy-driven interventions such as collaborative governance models, digital infrastructure investment, and capacity-building initiatives. However, significant gaps remain in the literature, particularly regarding the experiences of low-income urban regions and the role of user behavior in shaping adoption outcomes. This study emphasizes the urgent need for policy alignment and infrastructural equity to ensure that the benefits of innovation are accessible and sustainable across diverse urban contexts. It concludes by advocating for context-sensitive, interdisciplinary research that bridges technological potential with systemic inclusiveness.